Hearing Your Feedback Loud and Clear: Students’ Voices of Audio Feedback in Virtual Writing Class - Sheila Anjarani; Miftahul Furqon (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
There are many growing types of research about technology-supported feedback in English language teaching. Meanwhile, the study investigating audio feedback in virtual writing class during emergency remote teaching is still underexplored. In order to fill the gap, this research aims at investigating students’ perceptions towards audio feedback in virtual writing class. It employs a qualitative research design. Six students were voluntarily interviewed in this study. Furthermore, their writing was also observed. The findings of this study revealed that students view audio feedback positively. They admit that audio feedback is clear, personal, and detailed. Furthermore, students can feel the teaching presence because of the audio feedback. The further implications are discussed in this paper.